Impact of Distance Learning through Zoom Application and WhatsApp Group on Students’ Attitude and English Aptitude: A Case Study on Students of ICT due Covid-19 Outbreak - Fujiono Fujiono; Paulina paulina; Nurul Hidayati; Farah Natchiar (Kontribusia : Research Dissemination for Community Development, 2021)
This study was a case study of qualitative research design to know the impact of distance learning through zoom application and WhatsApp group on students’ attitude and English aptitude: A Case Study on Students of ICT due Covid-19 Outbreak. The result of the study showed that most of the students’ attitude or response to the online learning using zoom application are less interesting, interactive, effective, efficient and energetic. It was also found that many troubles with their signal, and they often got limited internet package. Zoom meeting needed much internet package to connect between lecturer and learners in one meeting. In this case, the trouble networks and limited internet also often gave impact on students’ learning process, style, and strategy to enhance their English aptitude; listening and speaking competency. Meanwhile, the lecturer took the usage of WhatsApp group by sending voice notes and materials about reading and writing. No troubled networks to download and upload the reading and writing tasks during distance teaching and learning class. It needed a little internet to get the online materials. Based on the situation, almost all participants felt interesting to join reading and writing online class. Aside from that, they could enhance their own English aptitude; reading and writing proficiency. To against the highly infectious covid-19 pandemic, the distance learning has created their physic and mental health from fear, anxiety, panic, and the outbreaks of influenza. Learning from home is one of the solution to reduce the physical contact to large number of people. Distance learning has been referred to save educational young generation from the pandemic of covid-19 outbreak.